Bubbor Paddas: Culture & Language of Sambas Preservation Efforts in West Kalimantan - tijah, kha (The Pontianak State Institute of Islamic Studies, 2018)
Culture changes following human change. However, in the midst of these changes there are efforts that can be made by humans, so that the direction of change is as expected, in the sense that change does not occur freely. This article tries to look at how Sambas culture is preserved through the